Design and Implementation of Coffeeshop Management System Prototype Using Rapid Application Development - Singgalen, Yerik Afrianto (Journal of Information System Research (JOSH), 2024)
This research focuses on designing and implementing a coffee shop management system using the Rapid Application Development (RAD) methodology. Through meticulous planning, user-centric design, and rigorous testing, the system addresses the specific operational needs of coffee shops, including supplier management, inventory tracking, sales analysis, employee scheduling, and the optimization of coffee shop management through digital systems. Following the RAD methodology, the prototype design undergoes iterative stages such as requirement planning, user design, construction, and cutover. Integrating Geographic Information Systems (GIS) enhances functionality by providing spatial visualization of supplier and staff locations. Additional features such as menu management and equipment maintenance tracking contribute to operational efficiency. This study underscores the importance of technological solutions in streamlining coffee shop operations and optimizing decision-making. Future research will focus on refining the system based on user feedback and evolving business requirements to ensure its effectiveness.